Knowledge Development of the Beard Community through Socialization of Community Empowerment of Toga, Chili and Eggplant Plants - ‘Aisy , Qatrunnada Salsabila Rohadatul; Abror, M. (Universitas Muhammadiyah Sidoarjo, 2025)
The community service program in Jenggot Village, Krembung District, Sidoarjo Regency, aims to improve the welfare of village communities through empowering family medicinal plants (TOGA), chili and eggplant. This program is implemented with the KKN-T scheme and the theme